2017
DOI: 10.1016/j.jagp.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Schizophrenia: Cytokine Levels and Their Relationships to Demographic and Clinical Variables

Abstract: Objective Inflammation may play a role in the accelerated physical aging reported in schizophrenia though biomarker findings and associations with demographic and clinical factors are inconsistent. Design Cross-sectional, case-control design Setting Community-dwelling participants tested in an academic laboratory. Participants 95 outpatients with schizophrenia (mean age ± SD: 48.1 ± 10.2 yrs) and 95 demographically-comparable healthy comparison subjects (HCs) (mean age ± SD: 48.1 ± 12.1 yrs) Measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
58
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 108 publications
7
58
1
4
Order By: Relevance
“…Consistent with previous reviews and meta-analyses, 66,67 73% of these reports observed elevated levels of pro-inflammatory cytokines and chemokines in schizophrenia, including interleukin (IL)-6, 23,28,38,48 IL-1β, 38,57 tumor necrosis factor alpha (TNFα), 48 Eotaxin-1, 35,45 Eotaxin-2, 35 monocyte chemoattractant protein-1, macrophage inflammatory protein-1β, thymus-and activation-regulated chemokine, macrophage-derived chemokine, 45 and lower levels of the anti-inflammatory cytokine IL-2. 30 For TNF-α and IL-6, group differences were reduced and in some cases nonsignificant after controlling for potential confounds.…”
Section: Characteristics Of Reviewed Studiessupporting
confidence: 76%
See 4 more Smart Citations
“…Consistent with previous reviews and meta-analyses, 66,67 73% of these reports observed elevated levels of pro-inflammatory cytokines and chemokines in schizophrenia, including interleukin (IL)-6, 23,28,38,48 IL-1β, 38,57 tumor necrosis factor alpha (TNFα), 48 Eotaxin-1, 35,45 Eotaxin-2, 35 monocyte chemoattractant protein-1, macrophage inflammatory protein-1β, thymus-and activation-regulated chemokine, macrophage-derived chemokine, 45 and lower levels of the anti-inflammatory cytokine IL-2. 30 For TNF-α and IL-6, group differences were reduced and in some cases nonsignificant after controlling for potential confounds.…”
Section: Characteristics Of Reviewed Studiessupporting
confidence: 76%
“…57 Of the 11 articles, 3 reported effect sizes ranging from small to medium in size, for elevated levels in schizophrenia. 28,45,48 Other studies found no differences for C-reactive protein (CRP) 40 or intercellular adhesion molecule-1 (ICAM-1) 63 ; however, a more inclusive review and meta-analysis of all studies of CRP (without the specific study inclusion criteria that we used) has shown consistent elevations in CRP in schizophrenia. 68 Age Relationships Thirty-six percent of articles reported differential relationships between inflammation and age in schizophrenia and HCs.…”
Section: Characteristics Of Reviewed Studiesmentioning
confidence: 87%
See 3 more Smart Citations